A Space and Time Machine: Actuality Cinema in New York City, 1890s to c. 1905 - Walsh, John (2005)
Urban actuality films are short, single shot views of street scenes, skyscrapers or construction sites, or views from moving vehicles. They are, typically, regarded as simple filmic snap-shots. Conversely, early cinema is conventionally thought to be a complex hybrid medium, a crucible for the idea and representation of the modern. Through close, contextualised analysis of a series of New York films, this study addresses the discrepancy between the putative insubstantiality of actuality films and the evident complexity of early cinema. A hitherto overlooked historical coincidence of actuality cinema, the modernisation of New York and its intermedial culture is shown to provide both a subject and setting for filmmakers.